International Survey of Family Law : 2018 edition / edited by Margaret Brinig. - Brinig, Margaret F. (Intersentia, 2018)
The International Society of Family Law is an independent, international, and non-political scholarly association dedicated to the study, research and discussion of family law and related disciplines. The Society's membership currently includes professors, lecturers, scholars, teachers, and researchers from more than 50 different countries, offering a unique opportunity for networking within a truly international family law community. The International Survey of Family Law is the annual review of the International Society of Family Law. It brings together reliable and clearly structured insights into the latest and most notable developments in family law from all around the globe. Chapters are prepared by an international team of selected experts in the field, usually covering 20 or more jurisdictions in each edition. The 2018 edition addresses highly topical matters ranging from assisted reproductive technology and sterilisation to end-of-life issues and estate settlement. The authors explore legislative changes, common law developments and challenges of integrating customary law or multiple religious legal systems into pluralistic societies. It brings together established and highly regarded academics and judges, as well as emerging scholars. Margaret Brinig is the Fritz Duda Family Chair in Law and Fellow at the University of Notre Dame. She is an elected member of the American Law Institute and part of the Executive Council of the International Society of Family Law.